Reducing Cycle Time By Eliminating Waste In Refrigerator Factory Unloading Process - Dedy Khaerudin; Nirfison Nirfison; Rahman Soesilo (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
The lean approach is often used by manufacturing companies to increase productivity in the production area. In this case PT P, a manufacturing company that produces refrigerators, faces the same problem on the unloading process in the final assembly area. The unloading process is the operation to move the finished product from the production line and store it in the finished goods warehouse. Operators in the unloading area have tasks to unload finished products from conveyors which are connected directly from the assembly line and placing them on pallets. Due to the refrigerator is quite heavy a forklift has to use to move the full pallet to the finished goods warehouse which is located next to the unloading area. Once finished the forklift returns to the unloading area with the empty pallets and places them in the unloading area, to be refilled by the unloading operator. Based on the data taken, the cycle time in the unloading process was recorded to be varied and the highest was 33 seconds, exceeding the takt time that had been determined on the production line, which was 24 seconds. This means that there is waste that occurs in the unloading area. The long and unstable cycle time in the unloading process makes the production line disrupted because the conveyor often stops and causes productivity to drop. For this reason, it is necessary to analyze and improve the process with the Lean concept by reducing the existing waste, so that the cycle time becomes stable and smaller than the takt time.